NEUROMYELITIS OPTICA IN HIV: A CASE REPORT AND LITERATURE REVIEW. Issue 12 (15th November 2016) - Appleton, Jason P; Kenton, Anthony
Abstract : Neuromyelitis optica (NMO) is a rare autoimmune condition that preferentially causes inflammation of the optic nerves and spinal cord. There are scanty reports of NMO occurring in the setting of patients with Human immunodeficiency virus (HIV). We present a case and review the literature. A 49 year old lady of African descent with known HIV diagnosed in 2004 – compliant with her antiretroviral medication, Atripla – was admitted with a 3 week history of thoracic back pain, spreading paraesthesia and weakness involving both legs, and constipation. Examination revealed a spastic paraparesis, a sensory level at T3/4 on the right and reduced vibration sense to the iliac crests bilaterally. MRI spine revealed increased signal within the cord from T3–7 in keeping with a longitudinally extensive transverse myelitis. CSF was acellular with normal protein, glucose ratio and no organisms seen. Her CD4 count was stable at 220 with a suppressed viral load. She was treated with 3 days of 1 g methylprednisolone. Serum Aquaporin-4 antibodies were positive and so in discussion with the genitourinary team she received a prednisolone tail and was commenced on maintenance azathioprine. She was subsequently discharged home after in-patient rehabilitation and remains stable to date. Neuromyelitis optica can occur in patients with known HIV. The immunosuppressive management of this aggressive inflammatory condition in this context needs to be delicately balanced to prevent complications from either disease process.